The Operetta as the Media in Minimizing the Drug Abuse in Children - Wijayatri, Ratna; Lutfiyati, Heni; Santoso, Setyo Budi; Geovani, Cagiva; Farida, Farida; Husna, Asmaul (Universitas Muhammadiyah Surakarta, 2022)
Drug is a very important commodity for the community, but in the usage, it needs to be monitored to avoid the drug abuse and misusage. The Children and adolescents are prone to the drug abuse, the childhood and adolescence age is a period that is still unstable. Hence, it really guidance and coaching are needed. SDN Bumirejo 1 is a strategically located elementary school with an easy access from the outside, therefore, that the partners feel the need to gain knowledge related to the drugs early to foster awareness and prevent drug abuse earlier. The purpose of this activity is to provide knowledge and coaching to the elementary school students about drugs, especially; the dangers of misuse of drugs and drug abuse. The method used is the combination of active human development (CBIA) and The Children Operetta of pharmacists. The percentage of partners who understood (values> 80) related to drug use increased from 30% to 70%. The enthusiasm of the guardians of students and teachers are very high, the awareness of participants that the proper use of drugs they had to do to avoid the things that are not desirable and the bad possibilities that would happen to their children become the motivation in participating this program and make changes in things previously wrong in the use of drugs to be more precise in their use. The program becomes more complete with the Operetta that is presented by the students to deliver messages related to medicine in an interesting and memorable way. The enthusiasm of students is also very high in watching and understanding messages from the Operetta.